2004
DOI: 10.1074/jbc.m404136200
|View full text |Cite
|
Sign up to set email alerts
|

Orexins Acting at Native OX1 Receptor in Colon Cancer and Neuroblastoma Cells or at Recombinant OX1 Receptor Suppress Cell Growth by Inducing Apoptosis

Abstract: Classical growth factors for colon cancer cells have been extensively described including agonists of tyrosine kinase receptors such as epidermal growth factor and related proteins (1) or insulin-like growth factors (2). More recently, some G protein-coupled receptor (GPCR) 1 agonists such as peptide hormones (3-5), prostaglandins (6), or serine proteases (7, 8) have been shown also to promote colon cancer cell proliferation often through transactivation of the epidermal growth factor receptor (6, 8). These GP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
205
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 99 publications
(214 citation statements)
references
References 54 publications
5
205
4
Order By: Relevance
“…However, data on whether orexins regulate the growth of carcinoma cells are inconlcusive. Certain studies have found that orexins promote the growth of cancer cells (8,10), athough others have shown inhibitory effects (30,31). The different cell types used may be the reason for these conflicting results.…”
Section: Discussionmentioning
confidence: 94%
“…However, data on whether orexins regulate the growth of carcinoma cells are inconlcusive. Certain studies have found that orexins promote the growth of cancer cells (8,10), athough others have shown inhibitory effects (30,31). The different cell types used may be the reason for these conflicting results.…”
Section: Discussionmentioning
confidence: 94%
“…Informed patient consent was obtained, according to the French bioethics law (58), beginning August 6, 2004. Immediately after removal, the tissues were placed in 4°C oxygenated Krebs solution, and the mucosa was carefully stripped from the underlying compartment made of muscularis mucosae and submucosa as previously described (59,60). Fragments of 20-30 mg were cut out and pinned in Sylgard-coated Petri dishes and maintained in culture for 24 or 48 h in 2 ml RPMI 1640 medium (Invitrogen) containing 0.01% BSA and antibiotics (200 μg/ml streptomycin, 200 U/ml penicillin, 1% fungizone; Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
“…6). We made 2 hits with orexin-A and orexin-B which appear to be robust growth inhibitors (6). Orexins do not alter cell cycle but promote strong apoptosis by inducing cytochrome c release from mitochondria to cytosol and activation of caspase-3 and caspase-7 (6).…”
Section: Introductionmentioning
confidence: 99%